2020
DOI: 10.2337/db20-7-lb
|View full text |Cite
|
Sign up to set email alerts
|

7-LB: Insulin and Glucagon Coadministration in Type 1 Diabetes Prevents Hypoglycemia without Worsening Hyperglycemia

Abstract: Despite pharmacological and technical advances, risk of hypoglycemia remains the greatest impediment to optimal glycemia in type 1 diabetes (T1D) and there is increasing interest in how the opposing actions of insulin and glucagon (Gn) may be harnessed to optimize glycemic control. We studied T1D subjects (n=11; age 36±4y, gender M:F 5:6, BMI 25.0±0.7 kg/m2, disease duration 23±3y, A1C 7.0±0.3%, daily insulin dose 43±3u) on two occasions, under meal challenge conditions (liquid mixed meal, 100g carbohydrate) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…4B; Table 1). Fortuitously, this degree of impairment would predict a favorable balance of respective glucagon-and insulin signaling activities in a FP, as extrapolated from the prior co-infusion studies (30)(31)(32) and assuming functional independence of the constituent domains (below). To provide a broader context for assessment of the selected lc-glucagon, alternative positions for the lactam-bond formation [residues 9-13, 12-16, 16-20, 20-24, or 24-28] were evaluated without achieving the desired functional properties (Table S6).…”
Section: Fibrillation-resistant Glucagon Analogmentioning
confidence: 99%
See 2 more Smart Citations
“…4B; Table 1). Fortuitously, this degree of impairment would predict a favorable balance of respective glucagon-and insulin signaling activities in a FP, as extrapolated from the prior co-infusion studies (30)(31)(32) and assuming functional independence of the constituent domains (below). To provide a broader context for assessment of the selected lc-glucagon, alternative positions for the lactam-bond formation [residues 9-13, 12-16, 16-20, 20-24, or 24-28] were evaluated without achieving the desired functional properties (Table S6).…”
Section: Fibrillation-resistant Glucagon Analogmentioning
confidence: 99%
“…2A)-even in the face of a 35-fold increase in insulin concentration (29). Indeed, glucagon-stimulated hepatic glucose output has been observed to mitigate hypoglycemia following concurrent infusion of the two hormones at fixed molar ratios (30)(31)(32). Despite the elegance of this idea, its application is presently limited by the hormones' discordant pharmacokinetic/pharmacodynamic (PK/PD) properties (33,34) and incompatible formulation chemistries (31,35), necessitating separate SQ depots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cherrington and colleagues have reported that concurrent injection of both hormones both provides glycemic control and buffers hypoglycemia. Encouraging clinical results were presented at the 80th ADA meeting [ 193 ]. Related studies by Novo Nordisk (using different insulin/glucagon ratios) provided evidence that such dual hormone therapy can not only mitigate risk of hypoglycemia, but also insulin-induced weight gain [ 194 , 195 ].…”
Section: Next-generation Insulin Analogsmentioning
confidence: 99%
“…The interaction or relationship between insulin and diabetes is properly regulated via the insulin transduction pathway (Ho et al 2016). In diabetes patient, this pathway which is abnormally increasing the absorbance of glucose into fat and muscle cells, as well as dysfunctional glycogenesis of glycogen in liver by glucagon (McCrimmon and Sherwin 2010;Bode et al 2020).…”
Section: Diabetes Diseasementioning
confidence: 99%